The Effects of Principal Leadership Style and Teacher Competence on Instructional Quality in Public Elementary Schools across Suak Tapeh District, Banyuasin Regency - Sutikno; Yasir Arafat; Hery Setiyo Nugroho (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study analyzed the effects of principal leadership style and teacher competence on instructional quality in public elementary schools across Suak Tapeh District, Banyuasin Regency. A quantitative ex post facto design was employed. The population comprised 175 teachers, and 120 respondents were selected using the Slovin formula at a 5% margin of error and proportional probability sampling. Data were collected through Likert-scale questionnaires, documentation, and observation. The instruments were valid and reliable, with Cronbach's alpha coefficients of 0.901 for principal leadership style, 0.831 for teacher competence, and 0.926 for instructional quality. Data were analyzed through descriptive statistics, prerequisite tests, simple linear regression, and multiple linear regression using SPSS version 26. Principal leadership style had a positive and significant effect on instructional quality (B = 0.523; t = 6.834; p < 0.001; R2 = 28.4%). Teacher competence also had a positive and significant effect (B = 0.731; t = 8.377; p < 0.001; R2 = 37.3%). Simultaneously, both variables significantly predicted instructional quality (F = 49.617; p < 0.001; R2 = 45.9%), with the regression equation Y = 10.679 + 0.321X1 + 0.559X2. The findings demonstrate that sustainable improvement in instructional quality requires effective, learning-oriented principal leadership and continuous development of teachers' pedagogical, professional, social, and personal competence.